The Problem of Truth in the “Critical” Philosophy of History - Radžvilas, Vytautas (Problemos, 1986)
The article deals with the problem of truth in the “critical” philosophy of history. The formation of the so-called post-Hegelian philosophy was related with efforts to overcome “dogmatism” in the field of historical knowledge and gave rise to the problem of truth. However, the problem was not solved nor even formulated strictly enough during the 19th century. This explains to a great extent why the problem occupies such a prominent place in the modern philosophy of history. The representatives of French personalism were among those who tried to solve the problem. Their approach to the problem is analysed in the article, and the conclusion is drawn out of its deficiency for an adequate solution of the problem.